Patients With Coronavirus Disease 2019 Interstitial Pneumonia Exhibit Pancreatic Hyperenzymemia and Not Acute Pancreatitis. Issue 5 (May 2021) - Pezzilli, Raffaele; Centanni, Stefano; Mondoni, Michele; Rinaldo, Rocco F.; Davì, Matteo; Stefanelli, Rossana; Melzi d'Eril, Gianvico; Barassi, Alessandra
Abstract : Objectives: Gastrointestinal manifestations of coronavirus disease 19 (COVID-19) have been well established, but pancreatic involvement is under debate. Our aims were to evaluate the presence of acute pancreatitis in COVID-19 patients and to assess the frequency of pancreatic hyperenzymemia. Methods: From April 1, 2020, to April 30, 2020, 110 consecutive patients (69 males, 41 females; mean age, 63.0 years; range, 24–93 years) met these criteria and were enrolled in the study. The clinical data and serum activity of pancreatic amylase and lipase were assayed in all patients using commercially available kits. Results: None of the patients studied developed clinical signs or morphological alterations compatible with acute pancreatitis. However, it was found that 24.5% of the patients had amylase values above 53 IU/L and 16.4% had lipase values above 300 IU/L. Only 1 patient (0.9%) had both amylase and lipase values in excess of 3-fold the upper normal limit without clinical signs of pancreatitis. Conclusions: The presence of pancreatic hyperenzymemia in a patient with COVID-19 requires the management of these patients be guided by clinical evaluation and not merely by evaluation of the biochemical results.